Pengaruh kombinasi Surface Pre-Treatment dan waktu inisiasi penyinaran terhadap kebocoran Mikro Restorasi RMGIC di RSGM Provinsi Sumatera Selatan - Aisyah Humairah; Rinda Yulianti; Martha Mozartha (Intisari Sains Medis, 2018)
Background: Microleakage of RMGIC may occur due to smear layer interfere with the adhesion mechanism. Surface pretreatment to remove smear layer has been suggested. This study aims to evaluate the effect of combination surface pretreatment (dentin conditioner and acid-etch) and delayed light initiation on microleakage RMGIC restoration.Methods: Class V cavities were prepared on 32 maxillary premolars which have fulfilled inclusion criteria and randomly divided into 4 groups. Cavities were pretreated with dentin conditioner (group I and II) and acid-etch (groups III and IV). All cavities were restored with RMGIC and immediate light initiation (group I and III), delayed light initiation for 3 minutes (group II and IV). All specimens were thermo-cycled and immersed in Rhodamine-B 2% dye solution for 24 hours at 37Â° C. Specimens were sectioned parallel to the axis of the tooth and the extent of Rhodamine-B dye penetration was examined under a USB Digital Microscope.Results: Statistical analysis revealed significant differences between time initiation group (3 minutes and 0 minutes) (P < 0.05). T-test results showed a significant difference between groups I and IV and Group III and IV (P< 0.05).Conclusion: This study showed that there is no effect of the combined surface pretreatment and delayed light initiation on microleakage RMGIC restoration